Discursive Constructions of the Self in British Romanticism - Bode, Christoph (Romanticism and Victorianism on the Net, 2008)
AbstractThis essay examines how subjective identities are discursively constructed in William Blake and P.B. Shelley, making brief references to William Wordsworth, Samuel Taylor Coleridge, Lord Byron, John Keats, and Charlotte Smith. It is argued that, although the poets come up with strikingly divergent solutions to the challenge of self-modelling, they face the same fundamental problems of self-grounding, working as they do within the paradox-prone paradigm of a Romantic self that tries to constitute itself out of itself. Comparing these Romantic poets with twentieth-century poetic models of selfhood and identity in Robert Frost and Wallace Stevens, this essay provides a tentative answer to the question of whether we continue to operate within the Romantic framework of discursive self-construction or whether in fact we have moved beyond this mode of self-construction.